Preparation and Characterization of Silver Nanoparticle by Cordia myxa Extract and their Study Anticancer, Antioxidant, Antibacterial Activity - Butheina A. Hasoon; Afnan I. Abdulwahab; Raghad Khwater Maeh; Khalida F. Al-azawi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The ethanolic extract leaves of the Cordia myxa plant were used to prepare the biosynthesis of silvernanoparticles (Ag-NPs). The detection of Ag-NPs was done using UV, FTIR, and SEM. We evaluated theanti-bacterial property of ethanolic and nano extract against the growth of two types of pathogenic microbes:Gram –ve bacteria (E. coli) and Gram +ve bacteria (S. aureus). The antibacterial activity of the nano extractwas high. In vitro, extracts demonstrated strong antioxidant activity against DPPH at a concentration of0.8mg/ml. The MTT test was utilized to detect the cytotoxicity of nano extract against lung tumor, and theresults indicated that nano extract treatment significantly inhibited the growth of cells (A594 cell line) ina concentration dependent manner. The results indicate, nano extract is a particularly valuable source ofantiproliferative and cytotoxic agents.